REBOOTING YOUR BRAIN using motivational intelligence to adjust your mindset, reach your goals, and realize unlimited success - Naylor, David (Leadership consultant) (JOHN WILEY & SONS, 2023)
Learn--and teach others--to embrace change and collaboration In Rebooting Your Brain: Using Motivational Intelligence to Adjust Your Mindset, Reach Your Goals, and Realize Unlimited Success, leadership development and sales expert, David Naylor delivers an incisive exploration of why people struggle and how to escape the shackles that hold individuals and organizations back. Leveraging the latest insights of cognitive psychology, neuroscience, and evolutionary biology, the book presents an easy to leverage framework that allows people to understand the exact steps necessary to let go the limiting beliefs and perspectives that create unhappiness, dissatisfaction and mediocrity. Relying on the author's unique and effective 2logical motivational intelligence-based solutions, readers will discover how to build greater success in both their career and personal life. Readers will also find: Explorations of what holds people back and how to remove those obstacles Strategies for promoting and encouraging accountability, open-mindedness, listening, reflection, engagement, and drive Techniques for reducing or eliminating risk aversion, closed-mindedness, negative attitudes, fear and instant gratification bias An essential and practical book perfect for team leaders, managers, executives, directors, and other business leaders, Rebooting Your Brain is the evidence- and cognitive science-based resource that leaders everywhere have been waiting for.